Effect of Autoclaving on Functional, Chemical, Pasting and Morphological Properties of - Babu, A Surendra; Parimalavalli, R (JOURNAL OF ROOT CROPS, 2014)
Starch is a major carbohydrate of sweet potato. Various attempts have been made to modify this highly flexible polymer with an aim to enhance the positive attributes of native starch. Hence in the present study, sweet potato starch was subjected to physical modification by autoclaving-cooling cycles. The effect of autoclaving on functional (water absorption capacity (WAC), oil absorption capacity (OAC), solubility, swelling power), chemical properties (amylose, protein, ash, pH, moisture and dry matter), pasting properties and morphological properties of sweet potato starch was evaluated. The results of functional properties showed that the WAC of autoclaved starch (AS) (3.95 g g-1) was higher than native starch (NS) (0.62 g g-1). The OAC was similar in native starch (0.73 ml g-1) and autoclaved starch (0.80 ml g-1). The swelling power of native and autoclaved starches from 50oC to 90oC ranged between 3.55-14.30 g g-1 and 4.56-6.26 g g-1 respectively. Solubility was in the range of 0.94-6.35 g g-1 for native starch and 0.68-1.47 g g-1 for autoclaved starch. A significant difference was noticed in functional properties between the starches. Amylose content increased by autoclaving from 18.56% (NS) to 24.98% (AS). Autoclaving increased protein (NS-0.20 g, AS-0.43 g), pH (NS-4.75, AS-5.95), while ash content decreased from 0.20% (NS) to 0.12% (AS). Significant difference was observed in chemical properties between starches. Autoclaving changed the pasting properties of starch. The peak viscosity of NS and AS was 4906 cP and 381 cP respectively and final viscosity was 3558.33 cP and 581.50 cP for NS and AS respectively. Significant difference was noticed in all the pasting properties of starches. Scanning Electron Microscopy (SEM) analysis revealed that autoclaving altered the native granular structure of sweet potato starch. The study showed that native sweet potato starch could be modified by autoclaving to obtain unique properties in food products.